DAMPAK PENERAPAN FINANCIAL TECHNOLOGY TERHADAP PENINGKATAN KINERJA UMKM - Ghina Febriana (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2025)
This study aims to analyze the ability of MSMEs in managing bookkeeping and financial statements, as well as evaluating the efficiency of transaction services to the community through the implementation of fintech. In addition, it also examines the advantages, disadvantages, and barriers to the use of fintech in Indonesia today. The Data used is secondary data in the form of documents obtained from various official agencies such as Bank Indonesia, OJK, BPS, Ministry of Cooperatives and SMEs, as well as previous scientific publications. The results showed that the application of fintech has a positive and significant impact on improving the performance of MSMEs, especially in digitizing books and financial statements that are more detailed and systematic. On the service side, features like QRIS are proven to increase efficiency, save transaction time, and increase customer satisfaction widely. Although it offers many benefits (such as access to P2P lending and e-wallets), fintech implementation is still constrained by limited internet networks, uneven smartphone ownership, and low technological and financial literacy of MSME actors. Therefore, regular education synergy is needed from the government and OJK to optimize the performance of the MSME digital economy